2015
DOI: 10.1152/ajpheart.00402.2014
|View full text |Cite
|
Sign up to set email alerts
|

Transglutaminase activity is decreased in large arteries from hypertensive rats compared with normotensive controls

Abstract: Watts SW. Transglutaminase activity is decreased in large arteries from hypertensive rats compared with normotensive controls. Am J Physiol Heart Circ Physiol 308: H592-H602, 2015. First published January 16, 2015; doi:10.1152/ajpheart.00402.2014 catalyze the formation of covalent crosslinks between glutamine residues and amine groups. This crosslinking activity has been implicated in arterial remodeling. Because hypertension is characterized by arterial remodeling, we hypothesized that TG activity, expression… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 20 publications
2
5
0
Order By: Relevance
“…Previous studies have shown that under basal conditions, TG2 stabilizes the contractile phenotype of SMCs and would thus support lower proliferation rates . TG2 protein expression is lost in the SMCs of hypertensive rats (corresponding to proliferative SMC phenotype) . These findings are supportive of our current results.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Previous studies have shown that under basal conditions, TG2 stabilizes the contractile phenotype of SMCs and would thus support lower proliferation rates . TG2 protein expression is lost in the SMCs of hypertensive rats (corresponding to proliferative SMC phenotype) . These findings are supportive of our current results.…”
Section: Discussionsupporting
confidence: 93%
“…51 TG2 protein expression is lost in the SMCs of hypertensive rats (corresponding to proliferative SMC phenotype). 52 These findings are supportive of our current results. However, in response to stress or growth factors, cell-surface TG2 can promote dedifferentiation and proliferation of SMCs.…”
Section: Discussionsupporting
confidence: 91%
“…In contrast, a reduced level of tissue transglutaminase in endothelial cells, obtained by their transfection with an antisense construct, decreased their spreading and adhesion strength, manifested by a lower resistance of these cells to trypsinization 46 . Besides, tissue transglutaminase is reduced in large arteries of hypertensive rats in comparison with control normotensive rats 49 . Also, in endothelial cells used in our study, the level of tissue transglutaminase might be reduced and might vary among the three cell lineages.…”
Section: Discussionmentioning
confidence: 85%
“…Recent evidence indicates altered TG2 activity and functionality in large arteries of hypertensive rats. 17 TG2 dysregulation has also been implicated in small-vessel changes and inward remodelling in hypertension. 18 Fundamental to many of the processes underlying ECM reorganization and fibrosis in aging and hypertension is activation of MMPs and TIMPs.…”
Section: The Ecm and Vascular Fibrosis In Aging And Hypertensionmentioning
confidence: 99%
“…Downstream signalling involves activation of redox-sensitive genes and transcription factors, early growth response factor-1, and activation of TGF-β1, MMPs, galectin-3, and MAP kinases. 57 , 58 , 59 , 60 , 61 The aging vasculature is characterized by increased levels of Ang II, 5 angiotensin-converting enzyme, 17 , 31 , 61 mineralocorticoid receptors, 62 and endothelin-converting enzyme-1. 63 , 64 As such, increased levels of these factors, their receptors, and downstream targets could represent an important event during aging that leads to vascular stiffness.…”
Section: The Role Of Prohypertensive Vasoactive Factors In Vascular Amentioning
confidence: 99%